Supporting tuberculosis program in active contact tracing: a case study from Pakistan - Babar Tasneem Shaikh; Ahmed Khan Laghari; Sulaiman Durrani; Alina Chaudhry; Nabeela Ali (BMC, 2022)
Abstract Tuberculosis (TB) is on the rise in Pakistan and there could be multiple reasons including poverty, difficulty in access to TB treatment services, non-compliance with treatment, social stigma etc. According to the TB program managers, limited treatment and testing sites for tuberculosis and lack of trained human resources play a major role in compromising TB management. A major lacuna in the TB control program is the absence of active contact tracing strategy. This is essential for a disease where positive cases are known to be able to infect a further 10‒15 individuals in a year. Tackling tuberculosis in Pakistan has been beleaguered by funding challenges and other systems' bottlenecks such as lack of skilled human resources and insufficient supply of medicines, despite the fact that disease burden is one of the highest in the world. Although it is a notifiable disease, active case finding, contact tracing and reporting is notoriously low throughout the country. Access to diagnostics and treatment facilities has been limited and stigma attached to the disease remains deeply entrenched among the communities. Researchers have shown that enhanced and active approaches to contact investigation effectively identifies additional patients with TB among household contacts at a relatively modest cost. USAID's Integrated Health Systems Strengthening and Service Delivery Activity extended support to the Health Departments of Sindh and Khyber Pakhtunkhwa provinces. In collaboration with the two provincial TB programs, community based active contact tracing was conducted on 17,696 individuals, based on the index cases. Among the contacts traced, 243 cases were diagnosed as drug sensitive or drug resistant TB. Awareness sessions were conducted to sensitize people on the various aspects of disease and importance of getting tested. The project also supported establishing three satellite Programmatic Management of Drug Resistant Tuberculosis (PMDT) sites for drug resistant TB treatment, enhancing the programs' diagnostic and testing capacity.